2015
DOI: 10.1371/journal.pone.0133745
|View full text |Cite
|
Sign up to set email alerts
|

Immortalisation with hTERT Impacts on Sulphated Glycosaminoglycan Secretion and Immunophenotype in a Variable and Cell Specific Manner

Abstract: BackgroundLimited options for the treatment of cartilage damage have driven the development of tissue engineered or cell therapy alternatives reliant on ex vivo cell expansion. The study of chondrogenesis in primary cells is difficult due to progressive cellular aging and senescence. Immortalisation via the reintroduction of the catalytic component of telomerase, hTERT, could allow repeated, longitudinal studies to be performed while bypassing senescent phenotypes.MethodsThree human cell types: bone marrow-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 79 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…Positive for ARS, APS, and Runx2 upregulation [71] Positive for ABS, TBS, and GAG assay in pellet culture [72]; low chondrogenic potential but stimulation of chondrocyte differentiation Positive for OROS, adipogenesis-related genes upregulation [71,73], and NRS [73] BMA13H Positive for ARS (reduced compared with primary cells) [74] Positive for ABS and GAG assay in 2D culture [74]; also positive for TBS, PSR and aggrecan and ColII immunostaining in 3D culture [75]; chondrogenic potential reduced compared with primary cells [74] Positive for OROS (reduced compared with primary cells) [74] SCP-1…”
Section: But Alsomentioning
confidence: 99%
See 3 more Smart Citations
“…Positive for ARS, APS, and Runx2 upregulation [71] Positive for ABS, TBS, and GAG assay in pellet culture [72]; low chondrogenic potential but stimulation of chondrocyte differentiation Positive for OROS, adipogenesis-related genes upregulation [71,73], and NRS [73] BMA13H Positive for ARS (reduced compared with primary cells) [74] Positive for ABS and GAG assay in 2D culture [74]; also positive for TBS, PSR and aggrecan and ColII immunostaining in 3D culture [75]; chondrogenic potential reduced compared with primary cells [74] Positive for OROS (reduced compared with primary cells) [74] SCP-1…”
Section: But Alsomentioning
confidence: 99%
“…It has been stated that hTERT transduction allows senescence evasion while maintaining in vitro and in vivo osteogenic ability of MSCs [63,91]. Transduction of hTERT alone has been employed to generate iMSC lines, but, since hTERT has no effect over non-replicative senescence, it has also been reported to fail to immortalize MSCs derived from bone marrow [13,18,58,74,104] and adipose tissue [85]. Skårn et al (2014) described that only one out of nine hTERT-transduced bone marrow-derived MSC clones was able to proliferate over 40 PDs, and even this clone showed a slow proliferation rate similar to that of primary MSCs [71].…”
Section: Immortalizing Human Adult Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed similar differentiation capacity in vitro between telomerized hMSC and primary hMSC. Whereas Dale and colleagues showed that hTERT transduction of HMSCs affected differentiation potential of the cells to varying degrees, several published studies reported that telomerization in a number of stromal cell populations maintain biological characteristics of the cells. Balducci and colleagues generated an adipose‐derived stromal cell line using transfection with hTERT and sv40 or HPV E6/E7 and the cells retained osteogenic and adipogenic differentiation potential.…”
Section: Discussionmentioning
confidence: 99%